Anti-ferroelectric composite film with high polarization intensity and low leakage current density as well as preparation method and application of anti-ferroelectric composite film
The antiferroelectric films composited with functional layer and lead zirconate layer were prepared by sol-gel method and spin-coating annealing process, which solved the problems of low polarization strength and high leakage current density of the existing films, and achieved high polarization strength and Low leakage current density effect, suitable for high-performance capacitors and memory.
Patent Information
- Application Number
- CN202411653541.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing inorganic capacitors and memory films have low polarization strength and high leakage current density, making it difficult to meet the needs of high-performance devices.
An antiferroelectric composite film composed of functional layers (tantalum pentoxide, zinc oxide or zirconium oxide) and lead zirconate layer was prepared by using the sol-gel method combined with spin coating annealing process.
It significantly improves the polarization strength of the film, reduces leakage current density, extends the service life of the device, and is suitable for the manufacturing of functional devices and flexible electronic devices.
Smart Images

Figure CN119400591A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic film capacitor and memory preparation, and specifically relates to an antiferroelectric composite film with high polarization intensity and low leakage current density, and a preparation method and application thereof. Background Art
[0002] Inorganic thin film materials have excellent electrical and optical properties and are widely used in dielectric, information storage, piezoelectric, optoelectronic and other fields. The current inorganic thin film preparation processes include sol-gel, chemical vapor deposition, anodic oxidation, magnetron sputtering, spray thermal decomposition, etc. Sol-gel process is widely used due to its high-quality film formation advantages. Inorganic antiferroelectric thin films have become a research hotspot in the field of dielectric capacitors and memory, but they still face the bottleneck problems of low polarization strength and high leakage current density of thin film materials. Therefore, it is urgent to prepare an antiferroelectric composite film with high polarization strength and low leakage current density. Summary of the invention
[0003] The purpose of the present invention is to solve the problem of low polarization strength and high leakage current density of existing inorganic capacitors and memory films, and to provide an antiferroelectric composite film with high polarization strength and low leakage current density, and a preparation method and application thereof.
[0004] An antiferroelectric composite film with high polarization strength and low leakage current density, which is composed of a functional layer and a lead zirconate layer;
[0005] The functional layer is one or more of tantalum pentoxide, zinc oxide or zirconium oxide.
[0006] A method for preparing an antiferroelectric composite film with high polarization strength and low leakage current density is specifically completed by the following steps:
[0007] 1. Preparation of functional layer precursor solution:
[0008] The functional layer precursor solution is one or more of a Ta2O5 precursor solution, a ZnO precursor solution and a ZrO2 precursor solution, and the preparation method is as follows:
[0009] ① Dissolve tantalum ethoxide in ethylene glycol methyl ether solution and stir at room temperature to obtain Ta2O5 precursor solution;
[0010] ②, dissolving zinc nitrate in ethylene glycol methyl ether solution, heating and stirring to obtain a ZnO precursor solution;
[0011] ③, dissolving zirconium n-propoxide in ethylene glycol methyl ether solution, stirring at room temperature to obtain a ZrO2 precursor solution;
[0012] 2. Preparation of lead zirconate precursor solution:
[0013] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred until it becomes clear to obtain a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0014] 3. Preparation of antiferroelectric composite thin films:
[0015] The functional layer precursor solution and the lead zirconate precursor solution are sequentially spin-coated on the substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film with high polarization strength and low leakage current density.
[0016] The invention discloses an antiferroelectric composite film with high polarization intensity and low leakage current density and is applied in inorganic film capacitors or memories.
[0017] Beneficial effects of the present invention:
[0018] 1. The present invention adopts a sol-gel method combined with a spin coating annealing process to prepare an antiferroelectric composite film with high polarization strength and low leakage current density; the functional layer is introduced into the lead zirconate antiferroelectric film, which reduces the leakage current density of the inorganic film, inhibits the polarization loss of the composite film, and improves the polarization strength of the composite film, which is beneficial to prolonging the service life of the device;
[0019] 2. An antiferroelectric composite film with high polarization strength and low leakage current density prepared by the present invention is used as a capacitor or memory, has low leakage current density and low polarization loss, is suitable for the design of functional devices, and is suitable for the manufacture of flexible electronic devices;
[0020] 3. The preparation process of an antiferroelectric composite film with high polarization strength and low leakage current density provided by the present invention is simple, the equipment is low-cost, the selected materials are environmentally friendly and pollution-free, and the harm of lead-based materials to human body and environment during production and use is overcome, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of the structure of an antiferroelectric composite film with high polarization strength and low leakage current density in the present invention;
[0022] Figure 2 XRD comparison spectra of the antiferroelectric composite films with high polarization intensity and low leakage current density prepared in Examples 1 to 3;
[0023] Figure 3 XRD comparison spectra of the antiferroelectric composite films with high polarization intensity and low leakage current density prepared in Examples 3 to 7;
[0024] Figure 4XRD comparison spectra of the antiferroelectric composite films with high polarization intensity and low leakage current density prepared in Examples 3, 8, 9, Comparative Example 1 and Comparative Example 2;
[0025] Figure 5 The hysteresis loop diagram of the antiferroelectric composite film with high polarization intensity and low leakage current density prepared in Examples 1 to 3;
[0026] Figure 6 The hysteresis loop diagram of the antiferroelectric composite film with high polarization intensity and low leakage current density prepared in Example 4-7;
[0027] Figure 7 The hysteresis loop diagrams of the antiferroelectric composite films with high polarization intensity and low leakage current density prepared in Examples 8, 9, Comparative Examples 1 and 2;
[0028] Figure 8 Leakage current diagram of the antiferroelectric composite thin film with high polarization intensity and low leakage current density prepared in Examples 3, 4, 5, and 7;
[0029] Fig. 9 Leakage current diagram of the antiferroelectric composite film with high polarization intensity and low leakage current density prepared in Examples 8, 9 and Comparative Example 1;
[0030] Fig.10 The leakage current diagram of the antiferroelectric composite film with high polarization intensity and low leakage current density prepared in Examples 1 and 2. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0033] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0034] Specific implementation method 1: This implementation method is an antiferroelectric composite film with high polarization strength and low leakage current density, characterized in that the antiferroelectric composite film is composed of a functional layer and a lead zirconate layer;
[0035] The functional layer is one or more of tantalum pentoxide, zinc oxide or zirconium oxide.
[0036] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the thickness of the functional layer is 10nm to 60nm, and the thickness of the lead zirconate layer is 260nm to 300nm. The other steps are the same as those of specific implementation method 1.
[0037] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: a method for preparing an antiferroelectric composite film with high polarization strength and low leakage current density is specifically completed by the following steps:
[0038] 1. Preparation of functional layer precursor solution:
[0039] The functional layer precursor solution is one or more of a Ta2O5 precursor solution, a ZnO precursor solution and a ZrO2 precursor solution, and the preparation method is as follows:
[0040] ① Dissolve tantalum ethoxide in ethylene glycol methyl ether solution and stir at room temperature to obtain Ta2O5 precursor solution;
[0041] ②, dissolving zinc nitrate in ethylene glycol methyl ether solution, heating and stirring to obtain a ZnO precursor solution;
[0042] ③, dissolving zirconium n-propoxide in ethylene glycol methyl ether solution, stirring at room temperature to obtain a ZrO2 precursor solution;
[0043] 2. Preparation of lead zirconate precursor solution:
[0044] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred until it becomes clear to obtain a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0045] 3. Preparation of antiferroelectric composite thin films:
[0046] The functional layer precursor solution and the lead zirconate precursor solution are sequentially spin-coated on the substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film with high polarization strength and low leakage current density.
[0047] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the concentration of the Ta2O5 precursor solution described in step 1① is 0.02mol / L to 0.03mol / L; the concentration of the ZnO precursor solution described in step 1② is 0.04mol / L to 0.06mol / L; the concentration of the ZrO2 precursor solution described in step 1③ is 0.04mol / L to 0.06mol / L. The other steps are the same as those of specific embodiments 1 to 3.
[0048] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the concentration of the lead zirconate precursor solution in step 2 is 0.2 mol / L to 0.4 mol / L. The other steps are the same as those of specific embodiments 1 to 4.
[0049] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the temperature of heating and stirring in step 1② is 60°C to 70°C; in step 2, heating and stirring at 60°C until clear; in step 3, the substrate is mica or Si substrate. The other steps are the same as those in specific embodiments 1 to 5.
[0050] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the spin coating process described in step 3 is: firstly spin coating at 1000 rpm, and then spin coating at 3500 rpm. The other steps are the same as those of specific embodiments 1 to 6.
[0051] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the drying temperature in step 3 is 400° C. to 430° C. and the drying time is 6 min to 10 min. The other steps are the same as those in specific embodiments 1 to 7.
[0052] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the annealing temperature in step 3 is 740° C. to 760° C. and the annealing time is 5 min to 10 min. The other steps are the same as those in specific embodiments 1 to 8.
[0053] Specific implementation method 10: This implementation method is an antiferroelectric composite film with high polarization strength and low leakage current density used in inorganic thin film capacitors or memory.
[0054] The following examples are used to verify the beneficial effects of the present invention:
[0055] Embodiment 1: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with a tantalum pentoxide layer (Ta2O5) and a lead zirconate layer (PbZrO3), and the preparation method is specifically completed by the following steps:
[0056] 1. Preparation of Ta2O5 precursor solution:
[0057] Dissolving tantalum ethoxide in ethylene glycol methyl ether solution and stirring at room temperature to obtain a Ta2O5 precursor solution;
[0058] The concentration of the Ta2O5 precursor solution described in step 1 is 0.025 mol / L;
[0059] 2. Preparation of lead zirconate precursor solution:
[0060] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0061] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0062] 3. Preparation of antiferroelectric composite thin films:
[0063] A layer of Ta2O5 precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (1Ta2O5-PZO) with high polarization strength and low leakage current density;
[0064] The substrate described in step 3 is a Si substrate;
[0065] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0066] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0067] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of the tantalum pentoxide layer (Ta2O5) is 10 nm, and the thickness of the lead zirconate layer (PbZrO3) is 270 nm.
[0068] Embodiment 2: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with a tantalum pentoxide layer (Ta2O5) and a lead zirconate layer (PbZrO3), and the preparation method is specifically completed by the following steps:
[0069] 1. Preparation of Ta2O5 precursor solution:
[0070] Dissolving tantalum ethoxide in ethylene glycol methyl ether solution and stirring at room temperature to obtain a Ta2O5 precursor solution;
[0071] The concentration of the Ta2O5 precursor solution described in step 1 is 0.025 mol / L;
[0072] 2. Preparation of lead zirconate precursor solution:
[0073] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0074] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0075] 3. Preparation of antiferroelectric composite thin films:
[0076] Two layers of Ta2O5 precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (2Ta2O5-PZO) with high polarization strength and low leakage current density;
[0077] The substrate described in step 3 is a Si substrate;
[0078] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0079] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0080] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of the tantalum pentoxide layer (Ta2O5) is 20nm, and the thickness of the lead zirconate layer (PbZrO3) is 270nm.
[0081] Embodiment 3: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is a lead zirconate layer (PbZrO3), and the preparation method is specifically completed by the following steps:
[0082] 1. Preparation of lead zirconate precursor solution:
[0083] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0084] The concentration of the lead zirconate precursor solution described in step 1 is 0.3 mol / L;
[0085] 2. Preparation of antiferroelectric composite thin films:
[0086] Four layers of lead zirconate precursor solution are spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (PZO) with high polarization strength and low leakage current density;
[0087] The substrate described in step 2 is a Si substrate;
[0088] The drying temperature in step 2 is 420°C and the drying time is 10 minutes;
[0089] The annealing temperature in step 2 is 750°C and the time is 10 min;
[0090] The thickness of the lead zirconate layer (PbZrO3) in the antiferroelectric composite film with high polarization intensity and low leakage current density described in step 2 is 270nm.
[0091] Embodiment 4: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with a zinc oxide layer (ZnO) and a lead zirconate layer (PbZrO3), and the preparation method is specifically completed by the following steps:
[0092] 1. Preparation of ZnO precursor solution:
[0093] Dissolving zinc nitrate in ethylene glycol methyl ether solution, stirring at 60° C., to obtain a ZnO precursor solution;
[0094] The concentration of the ZnO precursor solution described in step 1 is 0.05 mol / L;
[0095] 2. Preparation of lead zirconate precursor solution:
[0096] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0097] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0098] 3. Preparation of antiferroelectric composite thin films:
[0099] A layer of ZnO precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (1ZnO-PZO) with high polarization strength and low leakage current density;
[0100] The substrate described in step 3 is a Si substrate;
[0101] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0102] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0103] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of the zinc oxide layer (ZnO) is 15 nm, and the thickness of the lead zirconate layer (PbZrO3) is 270 nm.
[0104] Embodiment 5: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with a zinc oxide layer (ZnO) and a lead zirconate layer (PbZrO3), and the preparation method is specifically completed by the following steps:
[0105] 1. Preparation of ZnO precursor solution:
[0106] Dissolving zinc nitrate in ethylene glycol methyl ether solution, stirring at 60° C., to obtain a ZnO precursor solution;
[0107] The concentration of the ZnO precursor solution described in step 1 is 0.05 mol / L;
[0108] 2. Preparation of lead zirconate precursor solution:
[0109] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0110] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0111] 3. Preparation of antiferroelectric composite thin films:
[0112] Two layers of ZnO precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (2ZnO-PZO) with high polarization strength and low leakage current density;
[0113] The substrate described in step 3 is a Si substrate;
[0114] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0115] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0116] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of the zinc oxide layer (ZnO) is 30 nm, and the thickness of the lead zirconate layer (PbZrO3) is 270 nm.
[0117] Embodiment 6: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with a zinc oxide layer (ZnO) and a lead zirconate layer (PbZrO3), and the preparation method is specifically completed according to the following steps:
[0118] 1. Preparation of ZnO precursor solution:
[0119] Dissolving zinc nitrate in ethylene glycol methyl ether solution, stirring at 60° C., to obtain a ZnO precursor solution;
[0120] The concentration of the ZnO precursor solution described in step 1 is 0.05 mol / L;
[0121] 2. Preparation of lead zirconate precursor solution:
[0122] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0123] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0124] 3. Preparation of antiferroelectric composite thin films:
[0125] Three layers of ZnO precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (3ZnO-PZO) with high polarization strength and low leakage current density;
[0126] The substrate described in step 3 is a Si substrate;
[0127] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0128] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0129] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of the zinc oxide layer (ZnO) is 45 nm, and the thickness of the lead zirconate layer (PbZrO3) is 270 nm.
[0130] Embodiment 7: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with a zinc oxide layer (ZnO) and a lead zirconate layer (PbZrO3), and the preparation method is specifically completed according to the following steps:
[0131] 1. Preparation of ZnO precursor solution:
[0132] Dissolving zinc nitrate in ethylene glycol methyl ether solution, stirring at 60° C., to obtain a ZnO precursor solution;
[0133] The concentration of the ZnO precursor solution described in step 1 is 0.05 mol / L;
[0134] 2. Preparation of lead zirconate precursor solution:
[0135] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0136] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0137] 3. Preparation of antiferroelectric composite thin films:
[0138] Four layers of ZnO precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (4ZnO-PZO) with high polarization strength and low leakage current density;
[0139] The substrate described in step 3 is a Si substrate;
[0140] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0141] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0142] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of the zinc oxide layer (ZnO) is 60 nm, and the thickness of the lead zirconate layer (PbZrO3) is 270 nm.
[0143] Embodiment 8: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with zirconium oxide (ZrO2) and lead zirconate layer (PbZrO3), and the preparation method is specifically completed according to the following steps:
[0144] 1. Preparation of ZrO2 precursor solution:
[0145] Dissolving zirconium n-propoxide in ethylene glycol methyl ether solution and stirring at room temperature to obtain a ZrO2 precursor solution;
[0146] The concentration of the ZrO2 precursor solution described in step 1 is 0.05 mol / L;
[0147] 2. Preparation of lead zirconate precursor solution:
[0148] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0149] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0150] 3. Preparation of antiferroelectric composite thin films:
[0151] A layer of ZrO2 precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (1ZrO2-PZO) with high polarization strength and low leakage current density;
[0152] The substrate described in step 3 is a Si substrate;
[0153] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0154] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0155] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of zirconium oxide (ZrO2) is 10 nm, and the thickness of the lead zirconate layer (PbZrO3) is 270 nm.
[0156] Example 9: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with zirconium oxide (ZrO2) and lead zirconate layer (PbZrO3), and the preparation method is specifically completed according to the following steps:
[0157] 1. Preparation of ZrO2 precursor solution:
[0158] Dissolving zirconium n-propoxide in ethylene glycol methyl ether solution and stirring at room temperature to obtain a ZrO2 precursor solution;
[0159] The concentration of the ZrO2 precursor solution described in step 1 is 0.05 mol / L;
[0160] 2. Preparation of lead zirconate precursor solution:
[0161] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0162] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0163] 3. Preparation of antiferroelectric composite thin films:
[0164] Four layers of ZrO2 precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (4ZrO2-PZO) with high polarization strength and low leakage current density;
[0165] The substrate described in step 3 is a Si substrate;
[0166] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0167] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0168] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of zirconium oxide (ZrO2) is 40nm, and the thickness of the lead zirconate layer (PbZrO3) is 270nm.
[0169] Comparative Example 1: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with zirconium oxide (ZrO2) and lead zirconate layer (PbZrO3), and the preparation method is specifically completed by the following steps:
[0170] 1. Preparation of ZrO2 precursor solution:
[0171] Dissolving zirconium n-propoxide in ethylene glycol methyl ether solution and stirring at room temperature to obtain a ZrO2 precursor solution;
[0172] The concentration of the ZrO2 precursor solution described in step 1 is 0.05 mol / L;
[0173] 2. Preparation of lead zirconate precursor solution:
[0174] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0175] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0176] 3. Preparation of antiferroelectric composite thin films:
[0177] Two layers of ZrO2 precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (2ZrO2-PZO) with high polarization strength and low leakage current density;
[0178] The substrate described in step 3 is a Si substrate;
[0179] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0180] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0181] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of zirconium oxide (ZrO2) is 20nm, and the thickness of the lead zirconate layer (PbZrO3) is 270nm.
[0182] Comparative Example 2: An antiferroelectric composite film with high polarization strength and low leakage current density, wherein the antiferroelectric composite film is composited with zirconium oxide (ZrO2) and lead zirconate layer (PbZrO3), and the preparation method is specifically completed by the following steps:
[0183] 1. Preparation of ZrO2 precursor solution:
[0184] Dissolving zirconium n-propoxide in ethylene glycol methyl ether solution and stirring at room temperature to obtain a ZrO2 precursor solution;
[0185] The concentration of the ZrO2 precursor solution described in step 1 is 0.05 mol / L;
[0186] 2. Preparation of lead zirconate precursor solution:
[0187] Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred at 60° C. until it becomes clear, thereby obtaining a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution;
[0188] The concentration of the lead zirconate precursor solution described in step 2 is 0.3 mol / L;
[0189] 3. Preparation of antiferroelectric composite thin films:
[0190] Three layers of ZrO2 precursor solution and four layers of lead zirconate precursor solution are sequentially spin-coated on a substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film (3ZrO2-PZO) with high polarization strength and low leakage current density;
[0191] The substrate described in step 3 is a Si substrate;
[0192] The drying temperature in step 3 is 420°C and the drying time is 10 minutes;
[0193] The annealing temperature in step 3 is 750°C and the time is 10 minutes;
[0194] In the antiferroelectric composite film with high polarization strength and low leakage current density described in step 3, the thickness of zirconium oxide (ZrO2) is 30nm, and the thickness of the lead zirconate layer (PbZrO3) is 270nm.
[0195] Figure 1 A schematic diagram of the structure of an antiferroelectric composite film with high polarization strength and low leakage current density in the present invention;
[0196] from Figure 1 It can be seen that the composite film grows on the substrate and consists of two parts: the functional layer and the lead zirconate layer.
[0197] Figure 2 XRD comparison spectra of the antiferroelectric composite films with high polarization intensity and low leakage current density prepared in Examples 1 to 3;
[0198] Figure 3 XRD comparison spectra of the antiferroelectric composite films with high polarization intensity and low leakage current density prepared in Examples 3 to 7;
[0199] Figure 4 XRD comparison spectra of the antiferroelectric composite films with high polarization intensity and low leakage current density prepared in Examples 3, 8, 9, Comparative Example 1 and Comparative Example 2;
[0200] from Figures 2 to 4 It can be seen that there are obvious characteristic diffraction peaks in the film sample, and the film is in good crystallization condition.
[0201] Figure 5 The hysteresis loop diagram of the antiferroelectric composite film with high polarization intensity and low leakage current density prepared in Examples 1 to 3;
[0202] from Figure 5 It can be seen that after the introduction of the Ta2O5 functional layer, the antiferroelectricity of the inorganic film is weakened and the polarization strength of the film is improved. The polarization strength of the Ta2O5-PZO composite film can reach 140μC / cm 2 .
[0203] Figure 6 The hysteresis loop diagram of the antiferroelectric composite film with high polarization intensity and low leakage current density prepared in Example 4-7;
[0204] from Figure 6 It can be seen that after the introduction of the ZnO functional layer, the polarization loss of the inorganic film is greatly reduced, the hysteresis loop becomes thinner, and the polarization strength of the 2ZnO-PZO composite film is close to 250μC / cm 2 .
[0205] Figure 7 The hysteresis loop diagrams of the antiferroelectric composite films with high polarization intensity and low leakage current density prepared in Examples 8, 9, Comparative Examples 1 and 2;
[0206] from Figure 7 It can be seen that after the introduction of the ZrO2 functional layer, the antiferroelectricity of the inorganic film is weakened, the hysteresis loop becomes thinner, and the polarization strength of the 2ZrO2-PZO composite film is close to 120μC / cm 2 .
[0207] Figure 8 Leakage current diagram of the antiferroelectric composite thin film with high polarization intensity and low leakage current density prepared in Examples 3, 4, 5, and 7;
[0208] from Figure 8 It can be seen from the figure that after the ZnO functional layer is introduced, the leakage current of the inorganic film does not change much and remains at 10 -6 A or below.
[0209] Fig. 9 Leakage current diagram of the antiferroelectric composite film with high polarization intensity and low leakage current density prepared in Examples 8, 9 and Comparative Example 1;
[0210] from Fig. 9 It can be seen from the figure that after the introduction of the ZrO2 functional layer, the leakage current of the inorganic film is greatly reduced. Among them, the leakage current of 2ZrO2-PZO is close to 10 -9 A.
[0211] Fig.10 The leakage current diagram of the antiferroelectric composite film with high polarization intensity and low leakage current density prepared in Examples 1 and 2;
[0212] from Fig.10 It can be seen that after the introduction of the Ta2O5 functional layer, the leakage current of the inorganic film shows an upward trend and the insulation performance is slightly deteriorated.
[0213] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.
Claims
1. An antiferroelectric composite film with high polarization strength and low leakage current density, characterized in that The antiferroelectric composite film is composed of a functional layer and a lead zirconate layer; The functional layer is one or more of tantalum pentoxide, zinc oxide or zirconium oxide.
2. An antiferroelectric composite film with high polarization strength and low leakage current density according to claim 1, characterized in that The thickness of the functional layer is 10nm-60nm, and the thickness of the lead zirconate layer is 260nm-300nm.
3. The method for preparing an antiferroelectric composite film with high polarization strength and low leakage current density as claimed in claim 1, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of functional layer precursor solution: The functional layer precursor solution is one or more of a Ta2O5 precursor solution, a ZnO precursor solution and a ZrO2 precursor solution, and the preparation method is as follows: ① Dissolve tantalum ethoxide in ethylene glycol methyl ether solution and stir at room temperature to obtain Ta2O5 precursor solution; ②, dissolving zinc nitrate in ethylene glycol methyl ether solution, heating and stirring to obtain a ZnO precursor solution; ③, dissolving zirconium n-propoxide in ethylene glycol methyl ether solution, stirring at room temperature to obtain a ZrO2 precursor solution; 2. Preparation of lead zirconate precursor solution: Lead acetate is dissolved in ethylene glycol methyl ether, and the mixture is heated and stirred until it becomes clear to obtain a solution A; after cooling to room temperature, zirconium n-propoxide is added to the solution A, and the mixture is stirred to obtain a lead zirconate precursor solution; 3. Preparation of antiferroelectric composite thin films: The functional layer precursor solution and the lead zirconate precursor solution are sequentially spin-coated on the substrate, and then the wet film is dried on a flat heater and then placed in a rapid annealing furnace for rapid annealing to obtain an antiferroelectric composite film with high polarization strength and low leakage current density.
4. The method for preparing an antiferroelectric composite film with high polarization strength and low leakage current density according to claim 3, characterized in that The concentration of the Ta2O5 precursor solution described in step 1① is 0.02mol / L~0.03mol / L; the concentration of the ZnO precursor solution described in step 1② is 0.04mol / L~0.06mol / L; the concentration of the ZrO2 precursor solution described in step 1③ is 0.04mol / L~0.06mol / L.
5. The method for preparing an antiferroelectric composite film with high polarization strength and low leakage current density according to claim 3, characterized in that The concentration of the lead zirconate precursor solution described in step 2 is 0.2 mol / L to 0.4 mol / L.
6. The method for preparing an antiferroelectric composite film with high polarization strength and low leakage current density according to claim 3, characterized in that The heating and stirring temperature in step 1② is 60℃~70℃; in step 2, heating and stirring are performed at 60℃ until the mixture is clarified; and the substrate in step 3 is mica or Si substrate.
7. The method for preparing an antiferroelectric composite film with high polarization strength and low leakage current density according to claim 3, characterized in that The spin coating process described in step three is: first spin coating at 1000 rpm, and then spin coating at 3500 rpm.
8. The method for preparing an antiferroelectric composite film with high polarization strength and low leakage current density according to claim 3, characterized in that The drying temperature in step 3 is 400° C. to 430° C., and the drying time is 6 min to 10 min.
9. The method for preparing an antiferroelectric composite film with high polarization strength and low leakage current density according to claim 3, characterized in that The annealing temperature in step 3 is 740° C. to 760° C., and the annealing time is 5 min to 10 min.
10. The use of an antiferroelectric composite film with high polarization strength and low leakage current density as claimed in claim 1, characterized in that The invention discloses an antiferroelectric composite film with high polarization intensity and low leakage current density and is applied in inorganic film capacitors or memories.
Citation Information
Patent Citations
Composite structure high electric energy density thick film and preparation method thereof
CN103708848A
Energy storage film with high breakdown field strength and preparation method thereof
CN113493346A